DISEASES THAT OCCUR IN POTATO PLANTS GROWN IN HOUSEHOLDS (British Journal of Global Ecology and Sustainable Development, 2022)
Diseases of potato plants grown in the homesteads of the population were studied. This study was conducted mainly in Denov district.